2001
DOI: 10.1073/pnas.131171898
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear hormone receptor CHR3 is a critical regulator of all four larval molts of the nematodeCaenorhabditis elegans

Abstract: CHR3 (nhr-23, NF1F4), the homologue of Drosophila DHR3 and mammalian ROR͞RZR͞RevErbA nuclear hormone receptors, is important for proper epidermal development and molting in the nematode Caenorhabditis elegans. Disruption of CHR3 (nhr-23) function leads to developmental changes, including incomplete molting and a short, fat (dumpy) phenotype. Here, we studied the role of CHR3 during larval development by using expression assays and RNA-mediated interference. We show that the levels of expression of CHR3 (nhr-23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(147 citation statements)
references
References 54 publications
11
136
0
Order By: Relevance
“…Interestingly, inhibition of nhr-23, nhr-25, and lrp-1 gene expression also resulted in some morphological abnormalities. All these genes, including cpz-1, are highly expressed in the major hypodermal cells in all larval stages of nematodes, which supports their involvement in epidermal differentiation during or after molting (45,46,48).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Interestingly, inhibition of nhr-23, nhr-25, and lrp-1 gene expression also resulted in some morphological abnormalities. All these genes, including cpz-1, are highly expressed in the major hypodermal cells in all larval stages of nematodes, which supports their involvement in epidermal differentiation during or after molting (45,46,48).…”
Section: Discussionmentioning
confidence: 60%
“…The arrested L1-L2 worms were unable to shed their cuticle properly during molting as whole cuticles or parts of cuticle remained attached to the rectum (38,39). Soaking or feeding of all four larval stages of worms in nhr-23 dsRNA also resulted in molting defects, however, in the later developmental stages of the worms suggesting that nhr-23 may also regulate molting at each of the C. elegans larval developmental stages (47,48). So far, it is not clear whether both proteins have a direct function or their role is through downstream gene(s) that are not activated because of the nhr-23 or nhr-25 RNAi inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DAF-9 is unlikely to be the direct target regulated by Ce-imp-2. NHR-23 and NHR-25 are nuclear receptors, and NHR-25 is a homolog of mammalian FTZ-F1 receptor or FTZ-F1-like protein involved in regulation of cholesterol homeostasis (41)(42)(43). LET-512 is a member of the lipid kinase family that regulates localization and expression of Ce-LRP-1 in C. elegans (44).…”
Section: Discussion Presenilins and Impas: Two Related Families Of Prmentioning
confidence: 99%
“…So far, the regulatory mechanisms of C. elegans molting are not yet understood, although about a dozen genes have been identified that lead to molting defects when mutated. These genes can be classified into five categories based on their possible functions: (1) proteases that are used to degrade the old cuticle, including a cathepsin Z-like cysteine protease (Cecpz-1) (Hashmi et al, 2004), and two metalloproteases, nas-36 and nas-37 (Davis et al, 2004;Suzuki et al, 2004); (2) transcriptional regulators, including nhr-23 (Kostrouchova et al, 1998(Kostrouchova et al, , 2001, nhr-25 (Asahina et al, 2000;Gissendanner and Sluder, 2000), and let-19 (Wang et al, 2004); (3) enzymes involved in cholesterol metabolism such as let-767 (Kuervers et al, 2003) or cholesterol transporters such as lrp-1 (Yochem et al, 1999); (4) molecules involved in secretion and extracellular transport such as sec-23 (Roberts et al, 2003) and CeVps-27 (Roudier et al, 2005); (5) others, such as the angiotensin converting enzyme-like non-peptidase acn-1 (Brooks et al, 2003).…”
Section: Introductionmentioning
confidence: 99%